Obstetric and Neonatal Outcomes in Mild Idiopathic Polyhydramnios - Lucia Pasquini; Ilaria Ponziani; Marta Pallottini; Giulia Masini; Viola Seravalli; Carlo Dani; Mariarosaria Di Tommaso (MDPI AG, 2022)
Background: Idiopathic polyhydramnios is a controversial clinical condition, as data on perinatal outcomes are conflicting and vary depending on the severity of the condition. The aim of the present study was to compare obstetric and neonatal outcomes between pregnant women with mild idiopathic polyhydramnios and a control population. Methods: A retrospective cohort study was performed at a single university hospital comparing the obstetrics and neonatal outcomes of pregnancies with mild idiopathic polyhydramnios (n = 109) and control pregnancies (n = 2550). Results: Cesarean section (CS) was significantly increased in the group with polyhydramnios compared to controls (46% vs. 32%, respectively, p = 0.047) due to a higher rate of emergency CS in the polyhydramnios group (p = 0.041) because of abnormal cardiotocography (7.3% vs. 2.9%; p = 0.018) or labor dystocia (8.2% vs. 2.9%; p = 0.006). No statistically significant difference was found in the Apgar score, in the rate of neonatal hypoxia, or in the incidence of macrosomia between groups. In four cases, additional diagnoses of anomalies were made after birth, with a rate of 3.2%, which is comparable to the general population. Conclusion: Besides an increased risk of CS, patients with mild idiopathic polyhydramnios should be reassured regarding maternal and feto-neonatal outcomes. The management of pregnancies with stable mild idiopathic polyhydramnios should not differ from uncomplicated pregnancies, except for the need for increased labor surveillance.